Antioxidant, analgetic, and anti-inflammatory activity test of purple leaf ethanol extract (Graptophyllum pictum L. Griff) in vitro and in vivo - Ocvinta, Sisca; Dewi, Niluh Puspita; Utami, Indah Kurnia; Darmayanti, Darmayanti; Alaydrus, Syafika; Anwarudin, Wawang (Universitas Ahmad Dahlan, 2024)
Purple leaves are one of the plants that are widely used as medicine. Purple leaves have 3 types of plant varieties, namely purple leaves, green leaves, and white mottled leaves. Purple leaves have pharmacological activities that can be used as medicine, including antioxidants (improving the deterioration of cells in the body), anti-inflammatory (reducing or suppressing inflammation), antidiabetic (lowering blood glucose levels), analgesics (relieving pain), immunomodulators (increasing the work of the immune system in the body), antihemorrhoids (treating symptoms and complaints of hemorrhoids), and antibacterial (as an antiseptic). The purpose of this study was to determine the antioxidant activity of purple leaf ethanol extract (Graphtophyllum pictum (L.) Griff) in vitro using the DPPH method and to determine its effectiveness as an analgesic and anti-inflammatory against Wistar rats.The results showed that antioxidant activity showed an IC50 value of 72.31 ppm (strong antioxidant). Meanwhile, in the analgetic test, the highest percentage of analgesic effectiveness was found at a dose of 100 mg/kg BW (129.64%) and showed anti-inflammatory activity at a dose of 100 mg/kgBW with a percentage decrease in edem volume of 28.73% at the sixth hour.